2023
DOI: 10.3389/fendo.2022.1016804
|View full text |Cite
|
Sign up to set email alerts
|

Association of objective and subjective parameters of obstructive sleep apnea with plasma aldosterone concentration in 2,066 hypertensive and 25,368 general population

Abstract: Study objectivesObstructive sleep apnea (OSA) severity has been suggested in aldosterone elevation in resistant hypertension, whereas it is undetermined in the rest population. We explored the association of OSA parameters with plasma aldosterone concentration (PAC) in participants with and without hypertension.MethodsWe enrolled clinically hypertensive patients with polysomnography and PAC data under no interfering agents, compared (log) PAC, and assessed the linearity of log PAC by tertiles (T1/2/3) of sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Therefore, the aim of this study was to analyze the factors associated with elevated plasma aldosterone concentration (PAC) in community based population [ 21 , 22 ] by considering sex, since several studies have observed gender differences in levels and or regulators of aldosterone between men and women [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aim of this study was to analyze the factors associated with elevated plasma aldosterone concentration (PAC) in community based population [ 21 , 22 ] by considering sex, since several studies have observed gender differences in levels and or regulators of aldosterone between men and women [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As described previously [ 21 , 22 ], we used a multi-stage stratified sampling method to enroll study participants aged ≥ 18 years. At the first stage, Emin county was divided into three settings as urban, agricultural and stock-raising areas [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated the prevalence of poor sleep quality in various forms of hypertension, including idiopathic intracranial hypertension, metabolic syndrome-associated hypertension, and aldosterone-induced hypertension. [15][16][17][18] However, the causality between hypertension and poor sleep quality remains unclear, and further interventional studies may be required to elucidate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…An increased global prevalence of hypertension has paralleled increasing rates of obesity . Excess aldosterone production contributes to uncontrolled BP in patients with obesity and other associated diseases, such as obstructive sleep apnea and metabolic syndrome …”
Section: Introductionmentioning
confidence: 99%
“…4 Excess aldosterone production contributes to uncontrolled BP in patients with obesity and other associated diseases, such as obstructive sleep apnea and metabolic syndrome. [5][6][7][8][9][10][11] Contemporary guidance for treatment of resistant hypertension advocates for use of mineralocorticoid receptor antagonists (MRAs) following treatment with a 3-drug regimen of a thiazide-type diuretic, a dihydropyridine calcium channel blocker, and an angiotensin-converting enzyme inhibitor or angiotensin receptor blocker. 12 However, antiandrogenicand progestogenic-related adverse effects are common barriers to wider MRA use, particularly use of spironolactone.…”
mentioning
confidence: 99%